2010
DOI: 10.4269/ajtmh.2010.09-0336
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Recent Exposure to Phlebotomus argentipes, the Vector of Indian Visceral Leishmaniasis, by Using Human Antibody Responses to Sand Fly Saliva

Abstract: Antibody (IgG) responses to the saliva of Phlebotomus argentipes were investigated using serum samples from regions of India endemic and non-endemic for visceral leishmaniasis (VL). By pre-adsorbing the sera against the saliva of the competing human-biting but non-VL vector P. papatasi, we significantly improved the specificity of a P. argentipes saliva enzyme-linked immunosorbent assay. Using this method, we observed a statistically significant correlation between antibodies to P. argenitpes saliva and the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 16 publications
6
78
2
Order By: Relevance
“…As the EHCs were all close contacts of individuals with VL, we would expect a relatively high frequency of L. donovani infection (3). We also found that these individuals had significantly elevated serological titers of antibodies against P. argentipes saliva compared to the IGRA-negative EHCs or the NEHCs and were comparable to the individuals with active VL, presumably reflecting their greater exposure to sand fly bites and their greater risk of having been exposed to an infected sand fly (7). This finding lends some support to the argument that the EHCs who were scored positive in this assay represent a population of subclinically exposed, immune individuals.…”
Section: Discussionmentioning
confidence: 53%
“…As the EHCs were all close contacts of individuals with VL, we would expect a relatively high frequency of L. donovani infection (3). We also found that these individuals had significantly elevated serological titers of antibodies against P. argentipes saliva compared to the IGRA-negative EHCs or the NEHCs and were comparable to the individuals with active VL, presumably reflecting their greater exposure to sand fly bites and their greater risk of having been exposed to an infected sand fly (7). This finding lends some support to the argument that the EHCs who were scored positive in this assay represent a population of subclinically exposed, immune individuals.…”
Section: Discussionmentioning
confidence: 53%
“…aegypti saliva because previous studies have demonstrated that the IgG response is a useful biomarker for exposure to mosquito bites. 16,33,34 Further investigations are therefore needed to establish whether the antibody response to saliva is age dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous results obtained by Rohousova and others, 15 we found that all positive sera from naturally exposed children reacted strongly with a 30kDa protein, suggesting that this protein is the major immunodominant antigen of P. papatasi saliva in humans. Clements and others 33 recently highlighted the utility of measuring the antibody response to the saliva of Phlebotomus argentipes to assess the exposure among humans living in endemic areas for leishmaniasis and subsequently to evaluate vector control programs. However, these authors showed the possibility of cross-reactive reactions between different species of sand flies.…”
Section: 27mentioning
confidence: 99%